NKp46 enhances type 1 innate lymphoid cell proliferation and function and anti-acute myeloid leukemia activity - Rui Ma; Zhenlong Li; Hejun Tang; Xiaojin Wu; Lei Tian; Zahir Shah; Ningyuan Liu; Tasha Barr; Jianying Zhang; Sean Wang; Srividya Swaminathan; Guido Marcucci; et al. (Nature Communications)
Abstract NKp46 is a critical regulator of natural killer (NK) cell immunity, but its function in non-NK innate immune cells remains unclear. Here, we show that NKp46 is indispensable for expressing IL-2 receptor-α (IL-2Rα) by non-NK liver-resident type-1 innate lymphoid cells (ILC1s). Deletion of NKp46 reduces IL-2Rα on ILC1s by downregulating NF-κB signaling, thus impairing ILC1 proliferation and cytotoxicity in vitro and in vivo. The binding of anti-NKp46 antibody to NKp46 triggers the activation of NF-κB, the expression of IL-2Rα, interferon-γ (IFN-γ), tumor necrosis factor (TNF), proliferation, and cytotoxicity. Functionally, NKp46 expressed on mouse ILC1s interacts with tumor cells through cell–cell contact, increasing ILC1 production of IFN-γ and TNF, and enhancing cytotoxicity. In a mouse model of acute myeloid leukemia, deletion of NKp46 impairs the ability of ILC1s to control tumor growth and reduces survival. This can be reversed by injecting NKp46+ ILC1s into NKp46 knock-out mice. Human NKp46+ ILC1s exhibit stronger cytokine production and cytotoxicity than their NKp46− counterparts, suggesting that NKp46 plays a similar role in humans. These findings identify an NKp46–NF-κB–IL-2Rα axis and suggest that activating NKp46 with an anti-NKp46 antibody may provide a potential strategy for anti-tumor innate immunity.